Non-Financial Reporting and Legislative Technique - EU Requirements And Polish (In)Implementation –Legal-Comparative And Quantitative-Qualitative Analysis - Aneta TYLMAN; Agnieszka SKOCZYLAS-TWOREK; Marcin PODGÓRSKI (Communications of International Proceedings, 2022)
The article looks for answers to the question of whether the implementation of the EU regulations on non-financial reporting into the Polish legal regulations is sufficient and allows the realization of the objectives formulated in Directive 2014/95/EU of the European Parliament and of the Council of October 22, 2014 amending Directive 2013/34/EU as regards disclosure of non-financial and diversity information by certain large entities and groups. The methods used include legal-comparative and quantitative-qualitative analysis. The research objective was achieved through the analysis of legal UE and polish acts, literature sources, application of dogmatic and descriptive method, comparative methods and synthesis of research results. Results of the analysis showed that the legal regulation is not exhaustive and leaves entities free to interpret and publish this type of information. Hence, reports of operations are characterized by diversity that evolves over time and organization, and as such is criticized in the literature on the subject. This results in the provision of information and data that insufficiently reward business entities in conducting sustainable business may contribute to making inappropriate investment decisions. At the same time, the criticism of the doctrine of finance was mitigated by the postulates for further research on the part of both the doctrine of finance and financial law in order to further support legislative activities.
Keywords: non-financial reporting; non-financial disclosures; legislative technique